PENDIDIKAN AGAMA ISLAM DALAM MASYARAKAT MAJEMUK - L., Idrus (Institut Agama Islam Negeri (IAIN) Bone, 2023)
Islamic education in a plural society should be applied to educational institutions in Indonesia, the main requirement is to teach its value thoroughly without disturbing the others faith. A teacher, in interacting with other religious people is not only required to open up and respect them but he must commit to their religions. In the Koran, many records about the contact between Muslims with pre-existing celestial religions. Since the exsisting of Islam, it has been in the midst of other cultures and religions. The reality of pluralism is natural, differences in backgrounds and attitudes of people towards pluralism cannot be denied. By Islamic Education, it is expected to be able to provide enlightenment and foundation for the phenomenon of diversity and relations between nations, religion, culture, and so on.